THE IMPACT OF THE COVID-19 PANDEMIC ON MINORITY-OWNED HOSPITALITY BUSINESSES: A REVIEW OF EVIDENCE - Hill, Brian (Journal of Advance Research in Social Science and Humanities (ISSN 2208-2387), 2023)
Researchers have begun to assess the impact of the COVID-19 pandemic on African Americans and other minority groups. Multiple factors have together contributed to create a disproportionate impact of the pandemic on African Americans and other minorities. As a result, African American-owned businesses have had an 8% worse impact from COVID-19 compared to White-owned businesses. The current review was conducted to investigate the degree to which the COVID-19 pandemic affected minority-owned hospitality businesses. The review was conducted to fill a gap in the existing literature in which a synthesis of existing data suggesting the impact of the COVID-19 pandemic on minority- owned hospitality businesses was found lacking. Using a modified systematic literature review, I conducted an analysis of literature containing data relevant to understanding the impact of the COVID-19 pandemic on minority-owned hospitality businesses. After determining the scope of the review to extend to the hospitality industry, minority demographic, and minority-owned businesses, I used databases including Google Scholar, Scopus, and JSTOR with key terms including Covid-19 pandemic, hospitality industry, and minority-owned businesses. Findings showed that African American-owned businesses experienced the harshest blowback across all minority-owned businesses during the lockdown that occurred following the COVID-19 pandemic. Despite more African American-owned businesses applying for federal assistance, a smaller percentage of them received such assistance compared to White-owned businesses. Only 8% received full assistance, while 23% received no assistance whatsoever. The findings from the review supported previous research showing discrimination on a systematic level. Although small businesses owned by minorities added 1.3 million jobs within the U.S. economy between 2007-2012 during the Great Recession, they have received less support and faced systematic discrimination in availing financial assistance. It is imperative, in nation full of potentially successful entrepreneurs of color, to create an environment committed to helping them compete and succeed on an even playing field.